The EU’s Sanctions Against Russia in the Context of Russian Aggression on Ukraine, and Their Judicial Control - Matusiak-Frącczak, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
In 2014, the Russian aggression against Ukraine began and it escalated even greater in February 2022. The Western states, including the Member States of the European Union, reacted and introduced a wide variety of sanctions, first in 2014, then in 2022, yet until now they have not led to the termination of the Russian–Ukrainian conflict and to the withdrawal of the Russian troops from Ukraine. The aim of this article is to analyse these sanctions and their development as well as the judicial control that was effectuated in relation to these measures by the Court of Justice of the European Union.